2019
DOI: 10.3390/molecules24132499
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet-Induced Weight Loss is Associated with an Increase in Vitamin D Levels in Obese Adults

Abstract: Vitamin D is an important micronutrient involved in several processes. Evidence has shown a strong association between hypovitaminosis D and cardio-metabolic diseases, including obesity. A ketogenic diet has proven to be very effective for weight loss, especially in reducing fat mass while preserving fat-free mass. The aim of this study was to investigate the effect of a ketogenic diet-induced weight loss on vitamin D status in a population of obese adults. We enrolled 56 obese outpatients, prescribed with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 33 publications
2
57
0
5
Order By: Relevance
“…Notably, these results are in line with previous studies. A 2013 meta-analysis of 13 studies showed that body weight decreased significantly after VLCKD [ 15 ]. Similarly, Merra et al studied the effects of three types of VLCKD (all with carbohydrates intake <50 g/day) in 54 overweight/obese patients, observing a significant reduction in BMI, waist circumference, and total body fat after three weeks of VLCKD [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, these results are in line with previous studies. A 2013 meta-analysis of 13 studies showed that body weight decreased significantly after VLCKD [ 15 ]. Similarly, Merra et al studied the effects of three types of VLCKD (all with carbohydrates intake <50 g/day) in 54 overweight/obese patients, observing a significant reduction in BMI, waist circumference, and total body fat after three weeks of VLCKD [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A very interesting aspect to consider is the relationship between VLCKD and vitamin D. It is known that vitamin D levels are lower in obese people than in normal-weight subjects, possibly given volumetric dilution effects, but also due to other obesity-related factors, such as poor dietary intake, lack of exposure to sunlight, and lower skin synthesis [ 1 , 15 ]. Although the 2020 European Society of Endocrinology (ESE) guidelines about the work-up in obesity do not suggest the routine measurement of vitamin D levels in obese patients, its evaluation in patients undergoing VLCKD is of great interest since suboptimal levels seem to be associated with impaired glucose homeostasis, insulin resistance, and DM2 [ 15 ]. In our experience, we found that vitamin D levels become significantly increased after VLCKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the VLCKD group had a greater significant increase relative to the SHMD, from 18.4 to 29.3 ng/mL, p<0.0001 versus 17.5 to 21.3 ng/mL, p=0.067, as well as decreases in C reactive protein. 48 These results indicate the role of dietary macronutrient distribution on insulin secretion stimulus and its consequential effect on mitochondrial vitamin D hydroxylation activity and possible inflammation mediated depletion (usage) of vitamin D.…”
Section: Introductionmentioning
confidence: 73%
“…The second difference with vitamins A, E and K, is that there is no apparent storage organ or tissue for vitamin D or 25(OH)D. Although vitamin D is found in adipose tissue, suggesting that this is a storage site [5,6], it can only be released when stored fatty acids are mobilized to supply energy [7,8,9]. Thus, sequestered vitamin D in adipocytes cannot be a functional store, ready to be transported to the liver and converted to 25(OH)D, when circulating levels of this metabolite decline.…”
Section: Are the Lower Values In Winter Really An Indication Of Deficmentioning
confidence: 99%